2016
DOI: 10.1007/s10529-016-2165-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing and comparative analysis of Schizochytrium mangrovei PQ6 at different cultivation times

Abstract: The possible roles of PUFAs pathways, such as those mediated by fatty acid synthase, polyketide synthase, and desaturase/elongase, co-exist in S. mangrovei PQ6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…SZU445 was not observed to contain delta-12, delta-15, or delta-6 desaturases by whole-genome sequencing and protein annotation; however, it could synthesize PUFAs. A similar phenomenon has also been reported in a number of other studies, where Arthrospira platensis was observed to only have 15-cis-phytoene desaturase and zeta-carotene desaturase, and Strongylocentrotus nudus was observed to only have delta-5, delta-6, and delta-9 desaturases [41][42][43][44]. This result may indicate that the FAS pathway is not the primary pathway responsible for PUFA synthesis.…”
Section: Fatty Acid Synthesis By the Fas Pathwaysupporting
confidence: 84%
See 1 more Smart Citation
“…SZU445 was not observed to contain delta-12, delta-15, or delta-6 desaturases by whole-genome sequencing and protein annotation; however, it could synthesize PUFAs. A similar phenomenon has also been reported in a number of other studies, where Arthrospira platensis was observed to only have 15-cis-phytoene desaturase and zeta-carotene desaturase, and Strongylocentrotus nudus was observed to only have delta-5, delta-6, and delta-9 desaturases [41][42][43][44]. This result may indicate that the FAS pathway is not the primary pathway responsible for PUFA synthesis.…”
Section: Fatty Acid Synthesis By the Fas Pathwaysupporting
confidence: 84%
“…SZU445, but an isomerase and a DH were not identified; however, Thraustochytrium sp. SZU445 can also generate PUFAs such as DHA (C22:5) [42][43][44].…”
Section: Fatty Acid Synthesis By the Pks Pathwaymentioning
confidence: 99%
“…Minh Hien et al . 35 identified only two unigenes encoding elongase protein and one unigene encoding D6 desaturase. The missing of some specific enzymes might be the reason of the incomplete desaturation-elongation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Schizochytrium mangrovei cells were stained with 15-mM Nile Red (9-[Diethylamino]-5H-benzo[a]phenoxazin-5-one) prior to visualization by fluorescence microscopy as described by Hoang et al (2014). TEM analysis was performed as described by Hoang et al (2016).…”
Section: Methodsmentioning
confidence: 99%